Whole genome sequencing of Streptococcus suis revealed potential drug resistance and zoonotic transmission in companion cat - Lee, C.Y.; Selvarajah, G.T; Zakaria, Z.; Mustaffa-Kamal, F.; Gan, H.M; Voon, K.G.L; Fong, M.W.C; Ooi, P.T (Malaysian Society for Parasitology, 2024)
Streptococcus suis is a bacterium of clinical importance in diverse animal hosts including companion animals and humans. Companion animals are closely associated in the living environment of humans and are potential reservoirs for zoonotic pathogens. Given the zoonotic potential of S. suis, it is crucial to determine whether this bacterium is present among the companion animal population. This study aimed to detect Streptococcus suis in companion animals namely cats and dogs of the central west coast of Peninsular Malaysia and further characterize the positive isolates via molecular and genomic approach. The detection of S. suis was done via bacterial isolation and polymerase chain reaction assay of gdh and recN gene from oral swabs. Characterization was done by multiplex PCR serotyping, as well as muti-locus sequence typing, AMR gene prediction, MGE identification and phylogenomic analysis on whole genome sequence acquired from Illumina and Oxford Nanopore sequencing. Among the 115 samples, PCR assay detected 2/59 of the cats were positive for S. suis serotype 8 while all screened dog samples were negative. This study further described the first complete whole genome of S. suis strain SS/UPM/MY/F001 isolated from the oral cavity of a companion cat. Genomic analysis revealed a novel strain of S. suis having a unique MLST profile and antimicrobial resistance genes of mefA, msrD, patA, patB and vanY. Mobile genetic elements were described, and pathogenic determinants matched to human and swine strains were identified. Phylogenetic tree analysis on the core genome alignment revealed strain SS/UPM/MY/F001 was distinct from other S. suis strains. This study provided insight into the detection and genomic features of the S. suis isolate of a companion cat and highlighted its potential for antimicrobial resistance and pathogenicity.